Preferences of Gen Z Toward Islamic Fintech Services in The Digital Business Era - akbar f. ibrahim, mohamad; Saputera, Abdur (Jurnal Bisnis Digital & Perbankan, 2025)
This study examines Generation Z’s preferences toward Islamic fintech by analyzing their literacy levels, interest, perceptions of maqasid al-shariah, and trust and loyalty. The findings show that Islamic financial literacy is moderate (mean 3.12), indicating that Gen Z understands basic Sharia concepts but lacks deeper comprehension. Despite this, their interest in Islamic fintech is high (mean 4.21), driven by digital convenience and increasing religious awareness. Their perception of maqasid al-shariah implementation is also high (mean 3.85), reflecting positive views on transparency, fairness, and wealth protection within Islamic fintech services. Trust and loyalty score similarly high (mean 3.90), showing that security, platform reliability, and Sharia compliance play crucial roles in sustaining user engagement. Overall, the results highlight a gap between moderate literacy and high interest, emphasizing the need to strengthen education while maintaining service integrity. The study provides insights for industry players and regulators in enhancing Islamic digital finance.